Preparation of students-psychologists for analysis of social roles in inter-general interaction (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the analysis of the nature of social rolesin relations between grandparents and grandchildren. The author considersthe most important roles of the older generation in the family — guardians,counselors and consultants, friends, guardians of family traditions andfamily history. The purpose of empirical author’s analysis is to comparethe values of the functions and roles performed by the older generation inthe family and their impact on the life and development of grandchildren
Keywords: grandfathers; grandmothers; children; grandchildren; the nature of social roles; the nature of the relationship of older people; comfort in the family